Clinical Relevance of the Anti-inflammatory Effects of Roflumilast on Human Bronchus: Potentiation by a Long-Acting Beta-2-Agonist - Salvator, Hélène; Buenestado, Amparo; Brollo, Marion; Naline, Emmanuel; Victoni, Tatiana; Longchamp, Elisabeth; Tenor, Hermann; Grassin-Delyle, Stanislas; Devillier, Philippe (Frontiers in Pharmacology, 2020)
Background: Roflumilast is an option for treating patients with severe COPD and frequent exacerbations despite optimal therapy with inhaled drugs. The present study focused on whether the phosphodiesterase (PDE) 4 inhibitor roflumilast and its active metabolite roflumilast N-oxide affect the release of tumor necrosis factor (TNF)-α and chemokines by lipopolysaccharide (LPS)-stimulated human bronchial explants. We also investigated the interactions between roflumilast, roflumilast N-oxide and the β2-agonist formoterol with regard to cytokine release by the bronchial preparations. Methods: Bronchial explants from resected lungs were incubated with roflumilast, roflumilast N-oxide and/or formoterol and then stimulated with LPS. An ELISA was used to measure levels of TNF-α and chemokines in the culture supernatants. Results: At a clinically relevant concentration (1 nM), roflumilast N-oxide and roflumilast consistently reduced the release of TNF-α, CCL2, CCL3, CCL4, CCL5 and CXCL9 (but not CXCL1, CXCL5, CXCL8 and IL-6) from human bronchial explants. Formoterol alone decreased the release of TNF-α, CCL2, and CCL3. The combination of formoterol with roflumilast (1 nM) was more potent than roflumilast alone for inhibiting the LPS-induced release of TNF-α, CCL2, CCL3, CCL4, and CXCL9 by the bronchial explants. Conclusions: At a clinically relevant concentration, roflumilast N-oxide and its parent compound, roflumilast, reduced the LPS-induced production of TNF-α and chemokines involved in monocyte and T-cell recruitment but did not alter the release of chemokines involved in neutrophil recruitment. The combination of formoterol with roflumilast enhanced the individual drugs’ anti-inflammatory effects.